Emergent learning outcomes from a complex learning landscape. Issue 10 (3rd October 2021) - Bieluch, Karen Hutchins; Sclafani, Alexandra; Bolger, Douglas T.; Cox, Michael
Abstract: Institutions of higher education play an important role in training citizens who can thoughtfully and critically make decisions that impact the sustainability of our planet. While researchers have determined competencies that students need as environmental and sustainability professionals, less is understood about how to achieve these outcomes within complex learning environments, such as experiential learning settings. We apply a learning landscape framework to conceptualize connections among curricular and programmatic features and student learning outcomes on Dartmouth College's Environmental Studies Africa Foreign Study Program. We describe the results of 31 semi-structured interviews with alumni of the program. Results demonstrate that program design and pedagogical strategies, coupled with student activities, influence both cognitive and affective student learning outcomes, and that all learning elements are mutually influencing. Further, we identify two emergent learning outcomes, appreciation for reflection and introspection and capacity to engage with complexity, identified by considering learning at a landscape scale.